Six weeks of polarized functional interval training with large training load reductions does not affect performance gains compared to traditional workouts - Held, S.; Isenmann, E.; Rappelt, L.; Wiedenmann, T.; Kutschki, D.; Harbrecht, J.; Kirchner, K.; Geisler, S.; Donath, L. (Frontiers in Physiology, 2024)
Purpose: High-intensity functional interval training (HIFT) is predominantly composed of high exercise training intensities (HiT) and loads. Both have been linked to a higher risk of overtraining and injuries in inexperienced populations. A polarized training approach is characterized by high amounts of low-intensity training (LiT) and only approximately 5%-20% HiT. Compared to HIT-based training, this approach can result in temporary training load and intensity reductions without diminishing training gains. Thus, we aimed to examine the effects of traditional (TRAD) HIFT vs. polarized (POL) HIFT on relevant performance parameters.